(untitled) (Global Journal of Medical Research, 2020)
COVID-19 vaccine sample at Arctic Ocean and Antarctic Peninsula, plasmas from recovered people and CMV infected cetaceans, and modified MMR vaccines with the cetacean host. The present study proposes that the11-year cyclic sunspot number is analogous to a SWITCH, turning on and off an epidemic, inducing a public-health crisis. The ON period by the minimum (maximum) sunspot number initiated mutant viruses (AIV, SARS, MERS-CoV, and COVID-19) to transmit from the Poles to Continents by migratory birds and humpback whales. The first COVID-19 arrival dates in China, USA, Japan, Mexico, and Hawaii, determined by the distance between feeding grounds and breeding areas of humpback whale habitats. The OFF period occurs during the high sunspot number (>25-50) and may terminate COVID-19 in September (optimistic prediction) or in November, 2020 (pessimistic prediction) with three cases. Leather tanning industry (R 2 = 0.8514), global coastline (R 2 = 0.7864), USA coastline (R 2 = 0.3099), USA refinery (R 2 = 0.4874),CO 2 emissions (R 2 = 0.7627), population (R 2 = 0.3748), and minimum sunspot number (R 2 = 0.8907) showed high linearity with COVID-19 pandemic, as major causes in the 25worst-hit countries. COVID-19 can globally decrease by reducing toxic chemicals during the leather industry.